Civil Society, De-democratization and Political Polarization: The Hungarian, Polish, and Israeli Cases - Gerő, Márton (PARTECIPAZIONE E CONFLITTO, 2024)
This study aims to identify how civil society reacts to the de-democratizing attempts and the political polarization that usually accompanies this process. Civil society actors working under populist rule usually have to overcome two main challenges: the government's attempt to attack and co-opt civil society, and political polarization, which limits their social embeddedness, a crucially important criterion for resistance and maintaining their independence. I will examine the Hungarian, Polish, and Israeli cases and show how civil society organizations respond to the changing political context and how these responses might interact with political polarization. In each case, the paper introduces the policies and main legislative framework, funding and political discourse concerning civil society, and the responses of a diverse set of organizations (human rights, environmental protection, and civil society development organizations along with right-wing or pro-government civil society organizations). The main time frame of the analysis is between 2010 and 2020 for Hungary and Israel, and 2015-2020 for Poland, but in some accounts, I will also refer to developments between 2020 and 2023, using desk research and organizational interviews.